Here's the question you clicked on:

55 members online
  • 0 replying
  • 0 viewing

nilankshi

  • 4 years ago

(2x-1)(2x_3)+(3x-1)(3x-2)

  • This Question is Closed
  1. CoCoTsoi
    • 4 years ago
    Best Response
    You've already chosen the best response.
    Medals 1

    (2x-1)(2x_3) =(2x)(2x)-3(2x)-1(2x)+(-1)(-3) =4x^2 -6x -2x +3 =4x^2 -8x +3 (3x-1)(3x-2) =(3x)(3x)-2(3x)-3x+(-1)(-2) =9x^2 -6x -3x +2 =9x^2 -9x +2 (2x-1)(2x_3)+(3x-1)(3x-2) =4x^2 -8x +3 + 9x^2 -9x +2 =13x^2 -17x +5

  2. nilankshi
    • 4 years ago
    Best Response
    You've already chosen the best response.
    Medals 0

    thzz..

  3. Not the answer you are looking for?
    Search for more explanations.

    • Attachments:

Ask your own question

Sign Up
Find more explanations on OpenStudy
Privacy Policy